Factors associated with failure of humerus nonunion surgery in patients with initial nonoperative management - Alexander Hysong, MD; Noah Harrison, MD; Samuel Posey, MD; Ziqing Yu, MS; Andrew T. Chen, MD; Patrick Pallitto, MD; Joseph R. Hsu, MD; William Obremskey, MD; Evidence-Based Musculoskeletal Injury and Trauma Collaborative (EMIT); Hassan Mir, MD; Roman M. Natoli, MD, PhD; Ishani Sharma, MD, MBA; et al. (OTA International)
Abstract. Objectives:. To describe operative results after humerus nonunion surgery in patients whose initial humerus shaft fracture (OTA/AO code 12) was treated nonoperatively and to identify risk factors of nonunion surgery failure in the same population. Design:. Case series. Setting:. Nine academic level 1 trauma centers. Patients/Participants:. One hundred twenty patients with humerus nonunion whose initial fracture was treated nonoperatively. Intervention:. Operative treatment of humerus nonunions. Main Outcome Measurements:. Rate of recalcitrant nonunion after humerus nonunion surgery. Results:. Of 108 humerus nonunions, 26 (24.07%) failed to unite after nonunion surgery. Moreover, 34 patients (31.48%) experienced 1 or more postoperative complications. Multivariate analysis found that the use of bone graft or bone graft substitute was not associated with successful nonunion surgery (95% odds ratio confidence interval [CI] [0.67–5.3], P = 0.23). Tobacco use was associated with an increased risk of persistent nonunion (P = 0.0041). Postoperative complications (P = 0.0001) were also associated with an increased risk of persistent nonunion. Diabetes and open fracture were not associated with differences in the nonunion repair success rate. Conclusions:. As the largest and most generalizable to date, this multicenter study found that nearly 1 in 4 patients with a humeral nonunion after initial nonoperative management failed their nonunion surgical treatment. While postoperative complications were associated with recalcitrant nonunion, surgical adjuncts such as bone grafting and type did not seem to influence the success rate of nonunion surgery. Smoking is a modifiable risk factor suggesting that smoking cessation should be part of the intervention. These findings can be used to give patients and surgeons a realistic expectation of results and complications after humerus nonunion surgery. Level of Evidence:. Therapeutic level III.